PENGARUH ETIKA PROFESI, INDEPENDENSI, MOTIVASI, DAN PENGALAMAN AUDITOR TERHADAP KUALITAS AUDIT DI KAP KOTA MEDAN - Romanda Silalahi; Sauh Hwee Teng; Hantono Hantono (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This study aims to determine the influence of professional ethics, independence, motivation, and auditor experience on audit quality at Public Accounting Firms (KAP) in Medan City. This study uses a quantitative method with a descriptive and verification approach. The data used are primary data obtained through distributing questionnaires to auditors at several KAPs in Medan City. The number of samples in this study was 60 respondents selected using probability sampling techniques. The results of the study indicate that partially professional ethics has a positive and significant effect on audit quality with a significance value of 0.030. Independence also has a positive and significant effect on audit quality with a significance value of 0.041. Auditor motivation has a positive and significant effect on audit quality with a significance value of 0.020. Meanwhile, audit experience has a significant effect on audit quality with a significance value of 0.022. Simultaneously, professional ethics, independence, motivation, and auditor experience have a significant effect on audit quality with an F-value of 19.434 and a significance of 0.000. The Adjusted R1 Squared value of 0.556 indicates that 55.6% of audit quality can be explained by the research variables, while the rest is influenced by other factors outside the research.